2013
DOI: 10.1155/2013/836849
|View full text |Cite
|
Sign up to set email alerts
|

CD16+Monocyte Subsets Are Increased in Large Abdominal Aortic Aneurysms and Are Differentially Related with Circulating and Cell-Associated Biochemical and Inflammatory Biomarkers

Abstract: Proinflammatory components are present in abdominal aortic aneurysm (AAA). Circulating monocytes display heterogeneity, and three subsets have been identified, based on the differential expression for CD14 and CD16 receptors: CD14+CD16-, classical, CD14+CD16+, intermediate and CD14dimCD16+, non-classical monocytes. Increased proinflammatory CD16+monocytes with high expression of CD143 are present in CKD patients. D-dimer is increased in AAA patients, and might contribute to the pro-inflammatory response associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 51 publications
3
33
0
Order By: Relevance
“…The majority of monocytes express cell surface CD14 (CD14 + CD16 − ), whereas a minor subpopulation of monocytes also express the cell surface activation marker CD16, identifying them as more mature than the CD14 + CD16 − subpopulation. In agreement with previous studies [27], our data show that human peripheral blood monocyte subsets might be differentially distributed in AAA patients. Thus, CD14 ++ CD16 + monocytes were expanded, whereas proportion of CD14 ++ CD16 − monocytes was decreased in AAA-patients as compared with healthy individuals.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The majority of monocytes express cell surface CD14 (CD14 + CD16 − ), whereas a minor subpopulation of monocytes also express the cell surface activation marker CD16, identifying them as more mature than the CD14 + CD16 − subpopulation. In agreement with previous studies [27], our data show that human peripheral blood monocyte subsets might be differentially distributed in AAA patients. Thus, CD14 ++ CD16 + monocytes were expanded, whereas proportion of CD14 ++ CD16 − monocytes was decreased in AAA-patients as compared with healthy individuals.…”
Section: Discussionsupporting
confidence: 93%
“…CD16 + monocytes are thought to be the precursors of tissue-resident macrophages [21][22][23][24][25]. The CD16 + subset of monocytes increases significantly in chronic phagocytic conditions, such as atherosclerosis and AAA [26,27]. CD16 + consist of two subsets with distinct phenotypic and functional properties, namely, CD14 ++ CD16 + and CD14 + CD16 + cells.…”
Section: Introductionmentioning
confidence: 99%
“…89 Recent studies showed that patients with AAAs have increased levels of CD14 + CD16 + monocytes compared to control patients, suggesting these monocytes may be associated with the chronic inflammatory process of AAA. 90 CD16, a low affinity Fc receptor for IgG antibodies involved in antibody-dependent cytotoxicity, is also associated with an M1 macrophage polarization. 91 Experimental aneurysm models indicated that CD14 deletion reduced inflammatory cell infiltration therefore reducing AAA incidence.…”
Section: Macrophage Phenotypes: M1 and M2mentioning
confidence: 99%
“…ECM breakdown is a recruiter of monocytes, and the use of a monoclonal antibody has been shown to decrease this iniltration and prevent further ECM degradation [31]. Furthermore, the monocytes have demonstrated CD14 and CD16 cell surface marker positivity, and this patern is associated with M1 macrophage activation [32].…”
Section: Macrophagesmentioning
confidence: 99%